THE CHALLENGE OF ONLINE LEARNING IN CURRICULUM-2013 DURING COVID-19 PANDEMIC: STUDY OF SOCIAL SCIENCE TEACHERS AT MAN 2 PAREPARE - Fawziah Zahrawati; Nurhayati Nurhayati (Sociology Education, Teaching Training and Education Faculty, Muhammadiyah University of Kupang, 2021)
The COVID-19 pandemic has affected the structure of human life, including in the field of education. The government has established an online learning policy in an effort to suppress the spread of the virus. The application of online learning policies cannot be separated from various obstacles. One of them was experienced by a social studies teacher. This study aims to examine the obstacles to implementing online learning with the 2013 curriculum and the role of social studies teachers in overcoming them. The research method used is qualitative and implemented in MAN 2 Parepare, South Sulawesi. Data collection techniques are interviews and observation. To obtain the validity of the data, triangulation was carried out on methods, sources and theories. After that, the data were analyzed. This study found that the obstacles to the implementation of online learning with the 2013 curriculum were social inequality between students, limited online learning time, difficulty in assessing student learning processes and outcomes, and parents who did not accompany children in the learning process. The role of social studies teachers in overcoming these obstacles is to provide policies to students who have difficulty in learning online, use innovative learning methods, and try to establish communication with parents of students.